BIRDS OF SOUTHWESTERN BUNGO RANGE - Ng, Wen Teng; Mohamad Fizl Sidq, Ramji; Nadhirah Izzaty, Selamat; Isa, Sait; Rahah, Mohd Yakup; Mohd Hasri Al-Hafiz, Haba; Andrew Alek, Tuen (UNIMAS Publisher, 2023)
Bungo Range National Park (BRNP) is part of the Sarawak Kiri Catchment bordering Malaysia and Indonesia on Borneo, with coordinates of 1°16’0” N and 110°9’0” E (Figure 16.1). The Park is located at an elevation of 300 to 950 meters above sea level, covered by hill-mixed dipterocarp forest and few patches of tropical heath forest. It is surrounded by several Bidayuh villages, including Kampung Puak and Tringgus. The sampling location is located at the eastern site of the range, where it can be accessed from Tringgus, Bau. The natural scenery and biodiversity of this national park has now become the potential attractions to both local and foreign visitors. However, the current knowledge on the bird diversity in the Bungo Range National Park remains undocumented.